Conceptual Proposals for Environmental Investigations of Deep-seabed Mining - Hjalmar Thiel; Eric J. Foell; Gerd Schriever (International Marine Minerals Society)
Environmental studies for the mining of polymetallic nodules (PN) from the deep sea may be traced back for some 35 years.